Критичний аналіз таксономічного складу рідкісних судинних рослин у флорі Кіровоградської області - Shynder, Oleksandr (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2026)
Kirovohrad Oblast, located at the junction of the Forest-Steppe and Steppe zones in central Ukraine, has undergone significant anthropogenic transformation. Based on field surveys conducted by us between 1994 and 2025, a critical reassessment of published data, and an analysis of herbarium collections, the taxonomic composition of rare vascular plants in the flora of Kirovohrad Oblast has been evaluated. In total, 151 spontaneous plant species with international, national, or regional conservation status were documented, representing ca. 12.6 % of the estimated local flora. Among them, five species have high-priority conservation categories in the IUCN Red List, nine species are included in the Revised Appendix I of the Bern Convention, 65 species are listed in the Red Book of Ukraine, and 79 species appear in the List of vascular plant species subjected to special protection in the territory of Kirovohrad Oblast. Rare plants are unevenly distributed across the region: 80 species occur in the western, 118 in the northern, and 100 in the southern (steppe) parts of the oblast, with 133 species restricted to the Forest-Steppe zone, indicating higher floristic diversity in this part of the region. Based on new data and earlier findings, several species have been included for the first time among the rare plants of Kirovohrad Oblast, including Cephalanthera damasonium, Eremogone cephalotes, Odontarrhena tortuosa subsp. savranica, and Viola alba. A critical analysis of the List of vascular plant species subjected to special protection in the territory of Kirovohrad Oblast showed that not all species meet the criteria for regional-level protection. Some species listed as regionally rare in Kirovohrad Oblast are unconfirmed in the studied flora; two are alien, and three already have national or international conservation status. In total, 33 rare species have been erroneously or insufficiently justified as reported for Kirovohrad Oblast. Several proposals are offered to optimise the regional list of rare plants requiring protection in Kirovohrad Oblast, with special attention to the improved conservation of wetland and forest margin-range species, which are more vulnerable to present-day climate change. Examples of cultivating rare species are provided as an additional ex situ conservation measure.